Precarity and Resilience: The Sociology of Risk among Tobacco Farmers in Jember in Facing Ecological Crises and Price Uncertainty - Muhammad Abian Kholid; Rusmini Rusmini (International Conference on Islamic Economic (ICIE), 2026)
Tobacco farmers in rural areas are increasingly confronted with complex risks arising from ecological crises and price uncertainty, which directly affect the sustainability of their livelihoods. These conditions contribute to structural and recurrent precarity, particularly among smallholder farmers with limited resources and bargaining power. This article aims to analyze the forms of precarity experienced by tobacco farmers, the resilience strategies they develop, and the influence of market power relations and agrarian structures on farmers’ vulnerability and capacity to endure risk in Ampel Village, Wuluhan District, Jember Regency. This study employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation, and analyzed using thematic and interpretative analysis. The findings indicate that farmers’ precarity is shaped by the interaction between ecological crises, price fluctuations, and unequal agrarian power relations. In response, farmers develop social, economic, and cultural forms of resilience; however, these strategies tend to be adaptive rather than transformative and remain insufficient to address the structural roots of vulnerability. This study recommends policy interventions that not only strengthen farmers’ adaptive capacities but also promote improvements in market mechanisms and structural protection for tobacco farmers